A plethysmographic device for determining human body volume and body density - Cronjé, Thomas Frederick (Division of Biomedical Engineering, 2018)
The measurement of total body volume (V) (excluding lung volume) together with total body mass (m) is required in order to determine body density (d = m/V). From this, and using certain simplifying assumptions, it is possible to derive body composition in terms of fat mass (FM) and fat free mass (FFM) for the two-compartment model. The standard method for determining body volume (and hence body composition) is the densitometric (underwater weighing) technique based on Archimedes' principle. Three variables, notably residual lung volume (RV), total body mass (m) and submerged body mass are measured. RV is normally determined using a gas dilution technique while total body mass is simply measured using an accurate weighing scale. The submerged body mass is measured while the subject is totally submerged in a tank of water. This method, although relatively accurate, requires substantial apparatus and is time consuming. An alternative method, based on a polytropic thermodynamic process, is described for body volume measurement and thereby for body composition assessment. Previous use of this method by Taylor, et al. (1985) and Gundlach and Visscher (1986) were successful, but complex in terms of operating system. The described system comprises of a Perspex, sealed chamber. A cycling piston communicates with the chamber and imposes a minute sinusoidal pressure variation which is then measured. With a subject situated inside the chamber an increased pressure variation, caused by the decreased chamber volume, is then measured and processed to yield the displaced, or body volume. Subject comfort, above all, is greatly enhanced, in comparison to the underwater weighing method. A substantial advantage of the method appears to be that RV need no longer be measured. Variables such as a rise of temperature and humidity caused by the subject, as well as pressure variations due to respiration, were expected and found. These were analyzed both theoretically and experimentally and where necessary the data were modified to account for these variables using a personal computer. Calibration and preliminary validation of the instrument has been carried out using underwater weighing, bioimpedance and skinfold analyses and the error of measurement assessed. It appears that the described plethysmographic method is capable of measuring body volume and thus compares favourably to the underwater weighing method. Even though other groups have succeeded in employing similar principles, a substantially simpler mechanism has been used here.